Applicability of Adipose-Derived Stem Cells in Type 1 Diabetes Mellitus. Issue 3 (March 2015) - Lin, Hui-Ping; Chan, Tzu-Min; Fu, Ru-Huei; Chuu, Chih-Pin; Chiu, Shao-Chih; Tseng, Yu-Hsiung; Liu, Shih-Ping; Lai, Kuang-Chi; Shih, Mu-Chin; Lin, Zung-Sheng; Chen, Hsin-Shui; Yeh, Da-Chuan; et al.
Type 1 diabetes mellitus (T1DM) is a form of early onset diabetes mellitus characterized by the autoimmune destruction of insulin-producing cells (IPCs), resulting in hyperglycemia and abnormal glucose metabolism. There are currently no treatments available capable of completely curing the symptoms associated with the loss or functional defects of IPCs. Nonetheless, stem cell therapy has demonstrated considerable promise in the replacement of IPCs with immunomodulatory functions to overcome the defects caused by T1DM. Adipose-derived stem cells (ADSCs) are particularly suitable for use in cell transplantation therapy, especially when seeking to avoid the ethical issues and tumorigenic complications commonly associated with embryos or induced pluripotent stem cells. Cell-based treatments have demonstrated therapeutic advantages and clinical applicability of ADSCs in T1DM, ensuring their suitability for transplantation therapy. This manuscript focuses on the benefits and possible mechanisms in a T1DM-relevant model and displays positive results from finished or ongoing human clinical trials. We also discuss and hypothesize potential methods to further enhance the therapeutic efficacy of these efforts, such as a humanized rodent model and gene therapies for IPC clusters, to meet the clinical applicability of the standard.